Catastrophic success : why foreign-imposed regime change goes wrong - Downes, Alexander B., 1969- (Cornell studies in security affairs., 2021)
Interveners must recognize that, absent a rare set of promising preconditions, regime change often instigates a new period of uncertainty and conflict that impedes their interests from being realized.